공공기관 정보 공동이용기제의 법제도적 분석 - 정명주 (의정논총, 13(2), 2018)
본 연구에서는 약 50년의 역사를 갖는 전자정부 정책을 추진하는 가운데, 최근 협업과 소통의 근간이 되는 행정정보 공동이용 현황을 볼 때 행정기관과 달리 공공기관의 경우 정보 공동이용의 실적이 저조하다는 데 문제의식을 갖고 관련 법제도를 분석하였다. 분석결과, 현재의 전자정부법에 의한 규정으로는 공공기관의 정보 공동이용을 추진하는 데에는 한계가 있다는 점을 발견하고 3가지 대안을 제시하였다. 첫째안은 기존의 전자정부법내에 별도로 공공기관의 정보 공동이용에 대한 규정을 두어 강화하는 방안, 둘째는 전자정부법과 기획재정부 소관의 공공기관의 운영에 관한 법률등 소관이 다른 두 개의 각기 다른 법률에 두 개 소관기관간에 주도적인 역할과 협조역할을 설정하여 규정을 두는 방안, 세 번째는 정보 공동이용 뿐만 아니라 공공기관의 정보화 차원에서 기획재정부 소관의 공공기관 운영에 관한 법률에 공공기관의 운영과 정보화에 대한 내용을 통합하여 규정하는 안을 각 각의 안이 갖는 단점과 장점을 비교하면서 제시하였다. Through about 50 years’ e-Government policies, Korean e-government level is ranked first in the world. Particularly seeing the status of information-sharing that is basic mechanism of co-work and interconnection among organizations, government organizations achieved distinguished performances. Meanwhile, public organizations(public companies and pseudo-government organizations, from under PO) didn’t as much as government organizations. This study analysed the acts and institutions related to the information-sharing of PO. As a result, Electronic Government Act that controls the PO’s information-sharing is not enough to implement and promote the information-sharing of PO, and proposed three alternatives comparing weak points and strong points among them. One is to make separate chapter about PO’s information-sharing. Another is to put articles in each of the Electronic Government Act of the Ministry of the interior and the safety and the Act on the Management of Public Institutions. And the final one is to integrate articles of whole information policies and management in the Act on the Management of Public Institutions. KCI Citation Count: 0